Impact of maternal nutritional status on anemia in the third trimester of pregnancy - Febiana, Clarita Emilia; Siregar, Nursyahid; Astuti, Dewi Rinda; Jasmawati, Jasmawati (Poltekkes Kemenkes Yogyakarta, 2024)
Anemia during pregnancy remains a prevalent public health concern, particularly in low- and middle-income countries. Nutritional status, including body mass index (BMI), mid-upper arm circumference (MUAC), and gestational weight gain (GWG), is believed to play a crucial role in the development of anemia, especially during the third trimester when physiological hemodilution peak. This cross-sectional study was conducted among 53 pregnant women in their third trimester at the Bengkuring Samarinda Public Health Centre, Indonesia in 2023. Data were collected using structured questionnaires and clinical assessments. Nutritional status was assessed via BMI, MUAC, and GWG, while anemia was determined using hemoglobin levels. Statistical analysis included chi-square tests and Spearman correlation to determine the association between nutritional indicators and anemia incidence. A significant relationship was found between nutritional status and anemia. Underweight and overweight BMI were both associated with increased anemia prevalence (p < 0.05), indicating that extreme BMI values pose a risk. Women with low MUAC (indicative of chronic energy deficiency) showed a higher proportion of anemia (p = 0.046; r = –0.275). Inadequate GWG was also significantly related to anemia (p = 0.011; r = –0.345). Most anemic cases were classified as mild, with overweight and undernourished women exhibiting higher susceptibility due to impaired iron metabolism and suboptimal nutrient reserves. The findings support the hypothesis that maternal nutritional status significantly influences anemia in late pregnancy. The results emphasize the need for early identification of at-risk women based on BMI, MUAC, and GWG. These parameters can serve as simple, cost-effective screening tools in antenatal care settings to prevent adverse maternal and fetal outcomes. This study concludes that both undernutrition and overnutrition are significantly associated with anemia during late pregnancy. Monitoring maternal nutritional indicators such as BMI, MUAC, and GWG is essential in antenatal practice to reduce anemia-related complications.